PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP PERILAKU ETIS SERTA PENGARUHNYA TERHADAP KINERJA AUDITOR PEMERINTAH (Studi pada Auditor Pemerintah di Jawa Tengah) (E-logis : Jurnal Ekonomi Logistik, 2020)
Ethical behavior has been examined many times, but research in Indonesia that connects antecedents of ethical behavior to the auditors performance is limited and shows mixed results. The purpose of this study was to analyze the influence of spiritual intelligence and emotional intelligence on ethical behavior, and the impact on the performance of the internal auditor of Central Java provincial government. The research data was obtained from questionnaires distributed through census sampling method. Data were analyzed with methods of structural equation using Visual Partial Least Square (VPLS). The study provides empirical evidence that spiritual intelligence and emotional intelligence positively affects ethical behavior. Likewise, ethical behavior has positive effect on auditor performance. However, this study can not show the influence of spiritual intelligence and emotional intelligence on the performance of auditors.